2011
DOI: 10.1007/s00442-011-2167-x
|View full text |Cite
|
Sign up to set email alerts
|

Lemming winter habitat choice: a snow-fencing experiment

Abstract: The insulative value of early and deep winter snow is thought to enhance winter reproduction and survival by arctic lemmings (Lemmus and Dicrostonyx spp). This leads to the general hypothesis that landscapes with persistently low lemming population densities, or low amplitude population fluctuations, have a low proportion of the land base with deep snow. We experimentally tested a component of this hypothesis, that snow depth influences habitat choice, at three Canadian Arctic sites: Bylot Island, Nunavut; Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 21 publications
3
61
0
Order By: Relevance
“…Many parts of the Arctic receive less than 40 cm of snowfall during a winter, but this is often redistributed heavily by wind, creating a mosaic of habitat patches differing substantially in snow depth, with snow being trapped by topography and vegetation. A recent manipulation experiment that altered snow cover showed that increasing the snow depth in marginal winter habitat increased habitat use by small mammals in these areas, as expected, but the impact on demography (reproductive rate or mortality due to predation) was less clear 14 . Nonetheless, it is likely that change in snow depth or snow quality (e.g., increased amount of wet snow, icing, or collapses in the subnivean spaces, which increase the energetic costs incurred in getting access to food plants or in severe instances totally obstruct access) caused by climate warming will have a strong impact on small mammal population dynamics.…”
Section: Coping With a Changing Cryospherementioning
confidence: 60%
See 1 more Smart Citation
“…Many parts of the Arctic receive less than 40 cm of snowfall during a winter, but this is often redistributed heavily by wind, creating a mosaic of habitat patches differing substantially in snow depth, with snow being trapped by topography and vegetation. A recent manipulation experiment that altered snow cover showed that increasing the snow depth in marginal winter habitat increased habitat use by small mammals in these areas, as expected, but the impact on demography (reproductive rate or mortality due to predation) was less clear 14 . Nonetheless, it is likely that change in snow depth or snow quality (e.g., increased amount of wet snow, icing, or collapses in the subnivean spaces, which increase the energetic costs incurred in getting access to food plants or in severe instances totally obstruct access) caused by climate warming will have a strong impact on small mammal population dynamics.…”
Section: Coping With a Changing Cryospherementioning
confidence: 60%
“…The distribution of their winter nests show a strong association with deeper snow, and the greatest probability of occurrence is at snow depths from 60 to 120 cm 12,13 . A deep, dry snow cover reduces thermal stress on small mammals that overwinter in subnivean spaces, most notably by dampening the daily temperature fluctuations that they experience 12,14 . Many parts of the Arctic receive less than 40 cm of snowfall during a winter, but this is often redistributed heavily by wind, creating a mosaic of habitat patches differing substantially in snow depth, with snow being trapped by topography and vegetation.…”
Section: Coping With a Changing Cryospherementioning
confidence: 99%
“…Domine et al (2016a) showed at Bylot Island, in the Canadian High Arctic, that the highest snowpack thermal resistances were found in drifts and in willow shrubs, thus explaining quantitatively their suitability as a habitat for subnivean life. The temperature under deep snow is both higher and less fluctuating than under shallow snow (Duchesne et al 2011;Reid et al 2012), and temperature stability better predicts lemming presence than temperature per se (Duchesne et al 2011).…”
Section: Importance Of Snow and Ice For Tundra Wildlifementioning
confidence: 98%
“…The insulating properties of the snowpack are determined by its thickness and thermal conductivity. Collared lemmings (Dicrostonyx groenlandicus) and brown lemmings (Lemmus trimucronatus) studied in the High Arctic prefer areas with a snowpack ≥60 cm (Duchesne et al 2011) and are very apt at finding snow drifts (usually called snowbeds by ecologists; Reid et al 2012), often located on the leeward side of slopes or terrain with a rugged microtopography (Duchesne et al 2011) or in habitats where erect shrubs capture drifting snow. Although these areas may occupy a small proportion of the landscape, they are critical for the winter survival of these species.…”
Section: Importance Of Snow and Ice For Tundra Wildlifementioning
confidence: 99%
“…We used rows of snow fence on large grids (> 7 ha) to trap drifting snow during winter. In a previous paper, we showed that our manipulation increased snow depth on the experimental grids, created a more favourable sub‐nivean temperature regime and influenced the spatial distribution of lemming and vole winter nests (Reid et al 2012). Therefore, our manipulation improved the winter habitat quality of small mammals.…”
mentioning
confidence: 93%